HUKUM MELAKSANAKAN SALAT ID SECARA PERSONAL (MUNFARID) (SEBUAH SOLUSI PELAKSANAAN SALAT ID DI MASA WABAH COVID-19) - Akhmad Hanafi Dain Yunta; Asri, Asri (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
Id prayer is one of the prayers recommended to be done in congregation, but in abnormal conditions sometimes Muslims are prevented from conducting it in congregation, so it must be conducted in their homes either individually (munfarid) or in congregation with family members in one house. This study aimed to recognize the law of conducting id prayer at home in the midst of covid-19 outbreak. In this study the author employed library research method with a juridical normative approach to get accurate results from different perspectives described in numbers of works by classic scholars to be applied in the current situations. The results show that Id prayer may be done at home either individually or in congregation with family members in order to avoid the spread and transmission of covid-19.